Hotel Du Barry - Truffle, Lesley ([New York, NY] : HarperCollins, 2016)
Heartbreak, joy and nefarious doings at London's luxurious HOTEL DU BARRY. A book for lovers of fine gin, murderous impulses and writing of the ilk of Jonas Jonasson. When a laughing baby is found amongst the Hotel du Barry's billowing sheets, tucked up in an expensive pair of ladies' bloomers and neatly pegged to the laundry line, the hotel staff resolve to keep the child. The hotel's owner, Daniel du Barry, still mourning the loss of his lover in an automobile accident, adopts the little girl, names her after his favourite champagne and seeks consolation in fatherhood. Cat du Barry grows up beloved by both hotel staff and guests, equally at home in the ninth-floor premium suite as she is in the labyrinth below stairs. Years later when Daniel du Barry dies in sinister circumstances, Cat determines to solve the mystery with the assistance of her extended hotel family. From hotel detective to roguish Irish gigolo, from compassionate housekeeper to foxy chamber maid, each will play their wicked part in this novel that will charm, amuse and delight. PRAISE 'This is a wonderful romp of a novel, that brilliantly evokes the attraction and the dangers of the Jazz Age. There is plenty of fabulous fashion and empathetic characters - it cries out to be made into a film starring Helen Mirren' NZ Women's Weekly 'A must read' - Sunshine Coast Daily.
Imprint: HarperCollins.
Online resource; title from READ title page (OverDrive, March 2, 2016)
Keywords: Adoption -- Fiction; Detective and mystery stories; Fatherhood -- Fiction; Historical fiction; Mystery fiction; Adoption; Detective and mystery stories; Fatherhood; Fiction - General; Fiction & related items; FICTION / General; FICTION -- General; Australian; Fiction; Electronic books; Fiction